(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
The research paper analyzes and investigates the importance and role of regional cooperation in advancing supply chain resilience in Central Asia. By examining logistics performance metrics, trade volumes, and infrastructure investments, the study finds opportunities and mechanisms for improving logistics performance and supply chain resilience through regional cooperation and mitigating the risks. Findings reveal that regional cooperation, supported by international institutions, can open the potential of the region and can reduce logistics costs by up to 15%. Harmonized trade policies, digital custom systems, and shared infrastructure investments are recommended.